A facile synthesis of graphite-coated amorphous SiO2 from biosources as anode material for libs. (March 2023) - Askaruly, Kydyr; Yeleuov, Mukhtar; Taurbekov, Azamat; Sarsembayeva, Bibigul; Tolynbekov, Aidos; Zhylybayeva, Nurzhamal; Azat, Seitkhan; Abdisattar, Alisher; Daulbayev, Chingis
Abstract: The rapid pace of development of the world economy requires the progressive improvement of modern energy storage devices such as lithium-ion batteries (LIBs). The main limiting factor in the specific capacity of LIBs is the anode material, which is traditionally graphite. One possible solution is to use SiOx, which has a higher theoretical capacity than commercial carbon. Despite this, SiO2 has several disadvantages that limit its widespread use as an anode material for LIBs due to low electrical conductivity and short cycling life associated with volume changes during alloying–dealloying of lithium ions during charge-discharge. We have proposed an inexpensive and simple method for obtaining amorphous SiO2 particles in a carbon shell to solve these shortcomings. SiO2 was synthesized from biological waste material - rice husks, and the carbon shell was obtained from sucrose, which is also obtained from biomass. Surface morphology, structural analysis, and chemical composition were examined using XRD, thermogravimetric analysis, TEM, SEM, Raman and FTIR. The resulting composite shows a high performance of 450 mAh/g at a current density of 50 mA/g after 50 cycles and high cyclic stability compared to pure SiO2, which at 50 cycles showed 295 mAh/g at a current density of 50 mA/g. The proposed inexpensive and easily scalable method for obtaining a SiO2 /C hybrid composite is a possible solution for creating next-generation LIBs. Graphical Abstract: ga1 Highlights: A simple and easily scalable method for obtaining a SiO2 in a graphite shell for the LIB anode material is presented SiO2 /C composite was synthesized by facile method from biomasses. Physicochemical properties of SiO2 /C composite have been characterized and evaluated as an anode-active material for LIBs.